ISOLASI, IDENTIFIKASI DAN UJI SENSITIVITAS Penicillin G DAN Cefixime TERHADAP BAKTERI Staphylococcus epidermidis PADA SUSU MASTITIS SUBKLINIS DI SABRANG WETAN, WUKIRSARI, CANGKRINGAN - , ERVINA RYAN PUSPASARI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Mastitis is an inflammation of the mammary gland, can be occurred clinically or subclinically. One of the causes of mastitis is S. epidermidis. It is often, improper treatment with antibiotics can lead to bacteria resistance. This study was aimed to isolate and identify S.s epidermidis and to determine the sensitivity toward Penicillin G and Cefixime antibiotics. This study used 16 samples of milk and then tested with mastitis test with Californian Mastitis Test (CMT) reagent. Samples were inoculated in Brain Heart Infussion (BHI) and streaked on Blood Agar Plate (BAP) and Mac Conkey Agar (MCA) and then incubated for 24 hours at 37 o C. The colonies grew on the plate were identified based on the morphology and then streaked on the sugar medium and Nutrient Agar (NA). It was followed by Gramâs staining, catalase test, coagulase test, and DNase test to confirm the species of the bacteria. Sensitivity test was done by taking the colony of identified bacteria in the NA medium and then thawed with NaCl then streaked on the Muller Hinton Agar (MHA) and placed paper discs on it. Inhibition zones formed were can be measured after incubation for 24 hours at 37 o C. The result of the isolation showed that one of 15 samples (6,66%) was positive infected S. epidermidis. The result of the sensitivity test toward S. epidermidis showed that the bacteria 100% sensitive toward penicillin G and 100% resistant toward cefixime.